Otostegia persica (Lamiaceae): A review on its ethnopharmacology, phytochemistry, and pharmacology - Zahra Sadeghi; Maryam Akaberi; Jafar Valizadeh (Mashhad University of Medical Sciences, 2014)
Abstract Objective: The current study summarizes the updated information concerning the ethnopharmacology, Phytochemistry, and pharmacology of Otostegia persica Boiss. (Lamiaceae), an endemic medicinal plant in south and southeast of Iran. Materials and Methods: Information was collected through bibliographic investigation from scientific journals, books, theses, reports, and electronic search (databases SCOPUS, Google Scholar, Web of Science, and Science Direct). Moreover, documentation from unpublished resources and ethnobotanical surveys has been used. The present review covers the literature available from 2003 to 2013. Results: In traditional systems of medicine, this plant is reputed for treating diabetes, arthritis, gastric discomfort, headache, rheumatism, sedative activities, regulating blood pressure, and hyperlipidemia. Phytochemical screening of active components and mineral element evaluation of this species have been reported. Several types of diterpenoids and flavonols including morin, kaempferol, and quercetin are identified from the plant. Most of the pharmacological activity of this plant resides in its ﬂavonoid fraction which causes antimicrobial and antioxidant activities. Various pharmacological studies on O. persica show antimicrobial, antioxidant, anti-inflammatory, anti-diabetic, anti-aphid, and hepatoprotective activities. Conclusion: Being an endemic plant of Iran, this species is an important medicinal herb which can be used for various purposes. This review might be helpful for scientists and researchers to find new chemical entities responsible for its claimed traditional uses and discover new lead compounds for diseases mentioned.